2016
DOI: 10.1016/j.cyto.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of IL-15 dependent lymphocyte subsets in the liver

Abstract: IL-15 is a member of the gamma chain family of cytokines (γc – CD132). The IL-15 receptor (IL-15R) complex consists of 3 subunits: the ligand-binding IL-15Rα chain (CD215), the β chain (CD122; also used by IL-2), and the common γ chain. The biological activities of IL-15 are mostly mediated by the IL-15:IL-15Rα complex, produced by the same cell and ‘trans-presented’ to responder cells expressing the IL-15Rβγc. The peculiar and almost unique requirement for IL-15 to be trans-presented by IL-15Rα suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…IL-2Rα forms part of the IL-2 as well as the IL-15 receptor (in complex with IL-15Rα) (42). IL-15 is important for NK cell survival, activation and function (43,44), is strongly expressed in the liver (45)(46)(47), and hepatocyte-and KC-derived IL-15/IL-15Rα directly regulates the homeostasis of liver NK cells via trans-presentation (48). Conversely IL12RB, which encodes IL-12Rβ, is upregulated on cNK cells and induces IFN-γ production when stimulated by IL-12, highlighting that cNK and lrNK cells are regulated by different cytokines in the liver microenvironment (49).…”
Section: Activating the Lrnk Cell Immune Responsementioning
confidence: 99%
“…IL-2Rα forms part of the IL-2 as well as the IL-15 receptor (in complex with IL-15Rα) (42). IL-15 is important for NK cell survival, activation and function (43,44), is strongly expressed in the liver (45)(46)(47), and hepatocyte-and KC-derived IL-15/IL-15Rα directly regulates the homeostasis of liver NK cells via trans-presentation (48). Conversely IL12RB, which encodes IL-12Rβ, is upregulated on cNK cells and induces IFN-γ production when stimulated by IL-12, highlighting that cNK and lrNK cells are regulated by different cytokines in the liver microenvironment (49).…”
Section: Activating the Lrnk Cell Immune Responsementioning
confidence: 99%
“…Tissue specific ablation of IL-15Ra has revealed specific, but distinct patterns of requirement for the source of the transpresented IL-15 (18,19). We have shown IL-15 transpresentation by hepatocytes and macrophages is required for the maintenance of NK and NKT cells in the liver (20).…”
Section: Introductionmentioning
confidence: 73%
“…Hematopoietic and Non-Hematopoietic IL-15 Contribute to the Control of L. monocytogenes IL-15 from hematopoietic and non-hematopoietic cells are required for efficient activation of IL-15 dependent immune cells (7,19,20,48). To determine the relative contribution of IL-15 from the hematopoietic and non-hematopoietic compartments, we generated radiation chimeras and infected them with low dose L. monocytogenes two months after lethal radiation and hematopoietic reconstitution.…”
Section: Exogenous Ifng Partially Controls L Monocytogenes Infection In Il15-/-micementioning
confidence: 99%
“…Orthotopic liver transplantation experiments using IRF-1 knockout mice revealed that hepatocytes are major producers of soluble IL-15 and IL-15Rα complexes among liver cell populations [ 97 ]. A study using IL-15 knockout mice and IL-15Rα conditional knockout mice showed that hepatocyte-mediated IL-15 signaling by IL-15Rα expression is required to maintain the homeostasis of NK and NKT cells in the liver [ 98 ]. In turn, activated NK and NKT cells produce inflammatory cytokines such as IL-6, TNF, and IFN-γ.…”
Section: Liver-resident Natural Killer Cellsmentioning
confidence: 99%